A Retrospective Comparison on Europe and China Ecological Wisdom of Pre-Industrial Urban Communities of under the Lens of Sustainability Pillars - Casazza, Marco; Liu, Gengyuan; Maglioccola, Francesco; Lega, Massimiliano (Journal of Environmental Accounting and Management, 2026)
The design of a sustainable future for cities is of paramount importance, considering both the need of a societal transition and the fact that nearly half of the world's population is living within growing urban areas. While this process is generally driven the development of technological and socio-economic solutions, this work opted for a different approach. In particular, the existence of a prior urban sustainability wisdom was searched and assessed under the lens of the three known three pillars of sustainability (i.e.: environmental, economic, social). Wisdom is here considered as the application of a tacit knowledge oriented toward the stability of the urban environment and a city social and economic system. Focusing on the pre-industrial urban context in Europe and China, a review was conducted to collect and put together the evidence of such a wisdom. Results evidenced that the urban structure, the urban-rural gradient, food production and the management of water resources were carefully planned to guarantee the survival of the cities inhabitants. The problem of poverty alleviation, still remarked by the sustainable development goals, was already considered as a relevant factor for economy. Trade was anotther relevant element of urban development. Inclusion, belonging to the social dimension of sustainability, was also supported the mainainance of public spaces. Furthermore, the less-considered cultural factors, that are now regaining attention under the light of United Nations Framework Paris Agreement, played an important role, considering, for example, the birth and growth of universities. The present study, which would require further investigations about the socio-economic dimensions of sustainability, summarized the existence of the hypotesized sustainability wisdom, evidencing the importance of integrating the historical environmental and socio-economic dynamics to improve a sustainable urban planning. This research will need to be deepened trough archaeological, documental/historical and post-processual approaches, to address the need of transition toward a more equitable and sustainable post-fossil fuel societies within their urban context.